2017
DOI: 10.1016/j.bioactmat.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Smart biomaterials: Surfaces functionalized with proteolytically stable osteoblast-adhesive peptides

Abstract: Engineered scaffolds for bone tissue regeneration are designed to promote cell adhesion, growth, proliferation and differentiation. Recently, covalent and selective functionalization of glass and titanium surfaces with an adhesive peptide (HVP) mapped on [351–359] sequence of human Vitronectin allowed to selectively increase osteoblast attachment and adhesion strength in in vitro assays, and to promote osseointegration in in vivo studies. For the first time to our knowledge, in this study we investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 43 publications
1
36
2
Order By: Relevance
“…Lower circularity values indicate membrane protrusions, organization of cytoskeleton und migration tendency . Fibronectin and Vitronectin showed to have influence on human osteoblast adhesion and morphology, but were inferior to BSP‐coating with 50 µg/mL with regard to area coverage, aspect ratio and decreased circularity in our study. This leads to the conclusion, that BSP has a osteogenic property beyond that of other RGD‐containing proteins of the ECM.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Lower circularity values indicate membrane protrusions, organization of cytoskeleton und migration tendency . Fibronectin and Vitronectin showed to have influence on human osteoblast adhesion and morphology, but were inferior to BSP‐coating with 50 µg/mL with regard to area coverage, aspect ratio and decreased circularity in our study. This leads to the conclusion, that BSP has a osteogenic property beyond that of other RGD‐containing proteins of the ECM.…”
Section: Discussioncontrasting
confidence: 47%
“…We observed an increase in hOBs spreading area and an intercellular network formation on BSP coated CPC scaffolds in comparison to uncoated scaffolds, although cell number and viability were not different between the groups after longer incubation times ( und migration tendency. 49,50 Fibronectin and Vitronectin showed to have influence on human osteoblast adhesion and morphology, 49,50 but were inferior to BSP-coating with 50 mg/mL with regard to area coverage, aspect ratio and decreased circularity in our study. This leads to the conclusion, that BSP has a osteogenic property beyond that of other RGD-containing proteins of the ECM.…”
Section: Gene Expressioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In bone tissue engineering, the complex reactions occurred at the interface of the biomedical implants and the surrounding tissues determine the osseointegration and the long-term success of the implant [ 141 ]. A study demonstrated that osteoblast cell adhesion capacity to a glass and titanium surface was promoted by an adhesive peptide (HVP) grafts onto the surface of the materials [ 142 ]. Results suggested a significant increase of osteoblast adhesion when compared to a non-adhesive peptide and silanized glass after 2 h of culture.…”
Section: Nanostructured Film Surfacesmentioning
confidence: 99%
“…The issue consists of 8 papers covering different aspects related to smart biomaterials [1] , materials for 3D printing applications [2] , magnetic scaffolds [3] , nanocomposites [4] , bone cements [5] and several papers dedicated to biomedical coatings [6] , [7] , [8] .…”
mentioning
confidence: 99%